Analisis Keberlanjutan Integrasi Sawit-Sapi di Desa Purwodadi Kabupaten Tanjung Jabung Barat - Heruza Putra; Anis Tatik Maryani; Hutwan Syarifuddin (Universitas Batanghari Jambi, 2022)
The research was conducted in Purwodadi Village, Tebing Tinggi District, West Tanjung Jabung Regency, which is located on the easternmost coast of Jambi Province. Astronomically, Tanjung Jabung Barat Regency is located between 0053 - 01041 South Latitude and 103023 - 104021 East Longitude. The research location was chosen deliberately with the consideration that: (1) Purwodadi Village has an integrated system in the development of oil palm farming and cattle farming; (2) the pattern of raising oil palm-cow cattle by the people of Purwodadi Village is carried out semi-intensively; (3) the existence of an oil palm-cattle farming cultivation program in Purwodadi Village carried out by the government and farmer groups.